Cadeia de suprimentos inteligente: estudo de caso em uma empresa do subsetor de concentrados para bebidas não alcoólicas do Polo Industrial de Manaus - PIM - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The main objective of this work was to analyze the level of maturity of the supply chain of a company in the subsector of concentrates for non-alcoholic beverages of PIM, in the context of Industry 4.0. For that, a case study was carried out. The strategy used was quantitative-qualitative and descriptive research. At first, some maturity models were identified, where specific models for the intelligent supply chain were found. Being chosen the Maturity Model for Logistics 4.0, based on 07 dimensions proposed by Facchini (2020). The selected model focuses on evaluating the management and flow of material and information. Complementarily, interviews were carried out with a structured script with the company's managers, aiming to substantiate the information collected with the applied maturity model. The content of the interviews was treated through content analysis. The result obtained with the scale of the model presented the maturity level “Managing” for the dimensions Employees, IT Systems, Intelligent Products and Technologies; and “Adopting” maturity level for the dimensions, Knowledge, Strategy and Leadership and Intelligent Warehouses. The content of the interviews made it possible to ascertain the existence of a strong commitment to the digitization of the company's processes towards the Intelligent Supply Chain, with actions under development and ongoing investments. It was also possible to show that some operations were improved through systems used in connection with the enabling technology of Cloud Computing. However, there are still potentialities to be explored in the implementation of Industry 4.0 technologies, in the quest to achieve intelligence in Supply Chain Management.
Intelligent supply chain: case study in a company in the subsector of concentrates for non-alcoholic beverages in the Industrial Pole of Manaus - PIM
Keywords: Automação industrial; Cadeia de logística integrada; ENGENHARIAS::ENGENHARIA DE PRODUCAO; Indústria 4.0; Cadeia de Suprimentos Inteligente; Modelo de Maturidade